Use of various sugars in low sugar confectionery technologies - Tsaruk, Victoriia; Overchuk, Nataliya; Kambulova, Yuliia (My University, 2021)
This work is devoted to the study of the method of the production fruit and berry marmalade masses with the different kind of adding sugars. In this work we define the optimal conditions for the preparation of fruit and berry marmalade mass with glucose and fructose, carry out a comparative analysis of the organoleptic, physicochemical and structural-mechanical quality indicators of the marmalade mass with sucrose. Formulations of marmalade mass with apple puree, glucose and fructose have been developed. У роботі досліджено метод виробництва фруктово-ягідної мармеладної маси з додаванням різних видів цукрів. Визначено оптимальні умови приготування мармеладної маси з глюкозою і фруктозою, здійснено порівняльний аналіз органолептичних, фізико-хімічних та структурно-механічних показників якості маси з сахарозою. Розроблено рецептури мармеладної маси з яблучним пюре, глюкозою та фруктозою.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; berry; puree; marmalade; fructose; glucose; sucrose; gelification; фрукти; ягоди; пюре; мармелад; фруктоза; глюкоза; сахароза; гелеутворення; гелеутворення